2011
DOI: 10.1089/lap.2010.0455
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective, Randomized Study of Comparison of Clipless Cholecystectomy with Conventional Laparoscopic Cholecystectomy

Abstract: Ultrasonically activated scalpel can be used safely in laparoscopic cholecystectomy without risk of major injuries or leaks. It fairs better than electrocautery in terms of faster and safer surgery with decreased associated morbidity, less pain, and early return back home.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
57
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(67 citation statements)
references
References 12 publications
5
57
3
Order By: Relevance
“…The short-term outcome after the LC with the UsD in several trials shows that it could be a feasible and safe technique for routine cholecystectomy [4][5][6][7][8][9][10][11][12]. The results indicate that the UsD leads to a shorter mean operation time [5][6][7][8][9]20] and shorter mean hospital stay [14][15][16][17]12], less intraoperative blood loss [8][9][10], fewer intraoperative conversions, gallbladder perforations [5][6][7][8][9][10]12] and fewer postoperative intraabdominal fluid collections [8,9] and less bile leakage and postoperative abdominal pain and nausea [6,8,9,12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The short-term outcome after the LC with the UsD in several trials shows that it could be a feasible and safe technique for routine cholecystectomy [4][5][6][7][8][9][10][11][12]. The results indicate that the UsD leads to a shorter mean operation time [5][6][7][8][9]20] and shorter mean hospital stay [14][15][16][17]12], less intraoperative blood loss [8][9][10], fewer intraoperative conversions, gallbladder perforations [5][6][7][8][9][10]12] and fewer postoperative intraabdominal fluid collections [8,9] and less bile leakage and postoperative abdominal pain and nausea [6,8,9,12].…”
Section: Discussionmentioning
confidence: 99%
“…The ME technique is routinely used because of the ease of securing haemostasis and low costs. The ultrasonic dissection (UsD) has been used increasingly in endoscopic surgery [1][2][3] and the use of the UsD in the LC has been evaluated in some studies [4][5][6][7][8][9][10][11][12]. The results indicate that the UsD favours shorter recovery time [8,9,12] and fewer postoperative complications than the ME technique in the LC [5,[7][8][9][10]12].…”
Section: Introductionmentioning
confidence: 99%
“…[11] Now, laparoscopic cholecystectomy is considered to be the gold standard treatment for cholelithiasis. [12] Initially, this new technique was associated with a significant increase in morbidity, in particular iatrogenic biliary injuries and arterial haemorrhage. Anatomical relations on laparoscopic visualization are seen differently as compared to open surgery.…”
Section: Discussionmentioning
confidence: 99%
“…However, absorbable material can also act as a nucleus for subsequent bile duct stone formation until it is absorbed [5,18]. In the case of laparoscopic cholecystectomy, Jain et al have recommended the use of an ultrasonically activated scalpel instead of clips to decrease the chances of morbidity [19]. Tsumura et al revealed that the period between laparoscopic cholecystectomy and appearance of the first symptoms of clip migration ranged from 7 to 17 months [6,16].…”
Section: Discussionmentioning
confidence: 99%